KEJADIAN PERDARAHAN PADA PENGGUNAAN IUD POST PLASENTA - Herlyssa Herlyssa Herlyssa; Sri Mulyati; Theresia EVK (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
IUD Post placenta Insertion is an effort being made to the rate of population growth in Indonesia. Since the mid-2011- in June 2012 Tangerang District Hospital has been providing post-placental IUD services as much as 209 people consisting of 156 postplacental IUD insertion in post-cesarean section (74.7%) and 53 of the IUD Post placenta in normal delivery (25.3%). As with other postpartum IUD insertion, IUD Post placenta can cause side effects such as bleeding IUD. This study aims to determine the relationship of the use of IUDs Post placenta with bleeding events. This research is a quantitative study with case control design. The ratio of cases: controls is 1:4 so the number of cases as many as 15 people who experienced bleeding, while 60 people control the number of family planning acceptors IUDs Post Plasenta by 27 respondens (36%). The study reported that users of IUDs Post placenta bleeding by 40%. While that does not bleed nearly as much of that as much as 35%. Studies show no association between IUD use Post placenta with bleeding. So the program of insersion IUD Post placenta can be continued both vaginal delivery and perabdominan.